Transdisciplinarity and Reflective and Creative Thinking through Art in Teacher Training - María Dolores Soto-González; Ramona Rodríguez-López; Sonia Renovell-Rico (MDPI AG, 2023)
This article presents research on a creative and reflective thinking proposal conducted in the Early Childhood Education teaching degree program of the University of Valencia. The proposal was planned from a transdisciplinary perspective and combines art, technology and the Sustainable Development Goals from the 2030 Agenda. The study is linked to the Textile Cartographies international participatory project by the APECV (Association of Teachers of Expression and Visual Communication), in which 13 countries are involved. The research methodology is quantitative, using a validated questionnaire that helps evaluate the effectiveness of active transdisciplinary methodologies and art to promote reflective thinking. The total sample was composed of 117 students. The results of the questionnaire, which is structured into eight scales and a total of 48 items, reveal how activating reflective thinking leads to curiosity and surprise. This activation is driven by a transdisciplinary educational proposal which uses new technologies as a tool to create narratives and cartographies. In addition, importance is placed on cooperative group work, the contribution of ideas, and fostering creativity, giving value to experience for one's own professional future.